New perspectives on crime, violence and insecurity in Latin America - Schultze-Kraft, M.; Chinchilla, F. A.; Moriconi, M. (Crime, Law and Social Change, 2018)
This article introduces a Crime, Law & Social Change special issue on rethinking organised crime, collective violence and insecurity in contemporary Latin America. The five contributions, which among them cover the cases of Argentina, Brazil, Colombia, Guatemala and Mexico, address the puzzle of why and how in the midst of the world’s most serious crime and violence crisis ‘stability’ and ‘political order’ are nonetheless maintained. Taking a critical distance to conventional scholarship on these problems, the present collection of papers shifts the focus from one on how democratic regimes and formal institutions of the state are affected to a broader one that puts the spotlight on the ‘real politics’ and ‘real governance’ of crime and violence in the region. Cultural aspects of the ‘collapse of legality’, the holding power of informal institutions and the workings of ‘crimilegal orders’ and ‘criminalized electoral politics’ are explored through variegated conceptual and methodological approaches drawn from political science, criminology, sociology, social psychology, cultural studies and investigative journalism.